(untitled) (Bangladesh Journal of Microbiology, 2018)
Pollution of the environment and food with toxic heavy metals is being intensified in Bangladesh with industrial development. Consumption of foods and water contaminated with heavy metals imposes threat to human health. Aiming to find a solution to this problem, the present study focuses on probiotic Lactobacillus spp. with potential to remove heavy metals from environment as well as human body. A total of three Lactobacillus spp were isolated from curd samples and were identified based on their morphological and biochemical properties. These isolates were tolerant to low pH and bile salt which aids in their application in human gut. All isolates could tolerate 600 ppm chromium, 400 ppm lead, 400 ppm copper and 400 ppm zinc. The heavy metal tolerant Lactobacillus spp were also multi drug resistant and showed 100% resistance to Azithromycin, Cloxacillin, Gentamicin, Vancomycin, Streptomycin, Nalidixic acid, Trimethoprim-Sulfamethoxazole and Penicillin, while 100% sensitivity was observed to Imipenem. Bangladesh J Microbiol, Volume 34 Number 1 June 2017, pp 43-46